Injuries and specific medical support in Austrian youth athletes - a mixed-methods study - Reif, A.; Scharhag, J. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Already in youth competitive sport, high physical and mental demands in children and adolescence have been observed (Baur et al., 2008). Due to a large number of health-related issues adequate physical treatment and medical support is required. The aim of this study was to evaluate sports medical and performance assessment and especially of in young athletes.